2018
DOI: 10.1007/s40256-018-0269-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Branched-Chain Amino Acids on Serum Albumin Concentration in Heart Failure Patients with Hypoalbuminemia: Results of a Preliminary Study

Abstract: BackgroundWe conducted a randomized, controlled trial to determine whether supplementation with oral branched-chain amino acids (BCAAs) improves serum albumin and clinical outcomes in heart failure (HF) patients with hypoalbuminemia.Methods and resultsWe randomly assigned 18 in-hospital HF patients with serum albumin < 3.5 g/dL to receive oral BCAA granules (LIVACT®) for 28 days during their hospital stay or until discharge (BCAA group; N = 9) or to receive no supplementation (controls; N = 9), in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Recently, several studies have supported the influence of neuromuscular electrical stimulation therapy on improving physical function in HF patients, and its safety also has been confirmed 19 , 20 ) . In addition, other studies have indicated a beneficial impact of branched-chain amino acid (BCAA) supplementation for HF patients 21 , 22 , 23 , 24 ) , and a prospective study is currently being conducted to verify the combined effect of BCAA supplementation during conventional cardiac rehabilitation for Japanese HF patients 25 ) . Although these interventions are not routinely performed during rehabilitation of hip fracture patients, they may potentially be effective even for hip fracture patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have supported the influence of neuromuscular electrical stimulation therapy on improving physical function in HF patients, and its safety also has been confirmed 19 , 20 ) . In addition, other studies have indicated a beneficial impact of branched-chain amino acid (BCAA) supplementation for HF patients 21 , 22 , 23 , 24 ) , and a prospective study is currently being conducted to verify the combined effect of BCAA supplementation during conventional cardiac rehabilitation for Japanese HF patients 25 ) . Although these interventions are not routinely performed during rehabilitation of hip fracture patients, they may potentially be effective even for hip fracture patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, a very recent randomized, controlled trial conducted in in-hospital HF-patients demonstrated that supplementation with oral BCAA significantly improved hypoalbuminemia and the cardiothoracic ratio, which are common features of HF condition. 45 Moreover, BCAA treatment preserved cardiac function, prolonged survival, and increased gene expression related to mitochondrial biogenesis and function, in skeletal muscles in a HF-rat model. 46 …”
Section: Branched-chain Amino Acid As Biomarkers For Cvd Riskmentioning
confidence: 98%
“…For example, branched chain alpha-keto acids are elevated in hearts of heart failure patients, indicating that breakdown of branched chain amino acids (BCAA) is impaired. However, pharmacologic activation of BCAA catabolism and BCAA supplementation increased BCAA oxidation and improved cardiac contractility in heart failure patients and animal models ( 67 , 72 , 73 ). Cachexia is an independent risk factor for mortality during heart failure ( 74 ).…”
Section: Comparing Metabolic Pathways In Cancer and The Heartmentioning
confidence: 99%